Anxiety and Self-Reinforcement in Advanced Semester Students - Zainul Anwar; Silviana Nur Fajri (Psikologia : Jurnal Psikologi, 2015)
Students who have not completed their study within the specified time limit indicated that they have psychological problems during doing the final task that trigger their anxiety. While the anxiety experienced by Students correlated with the frequency of self-reinforcement against them. This study aimed to determine the differences in the level of anxiety in terms of the frequency of self-reinforcement to Students who exceed the time limit. This study used quantitative methods to collect comparative data through the Taylor's Manifest Anxiety Scale instrument and Frequency of Self Reinforcement Questionnaire. The number of subjects were 123 students. The results showed that there were differences in anxiety levels significantly between students who have a high frequency of self-reinforcement tostudents with low frequency of self-reinforcement.